Організація бухгалтерського обліку витрат, доходів і фінансових результатів суб’єкта господарювання - Карп’як, Я. С. (Видавництво Львівської політехніки, 2014)
Розглянуто принципи нарахування та відповідності доходів і витрат. Досліджено класифікацію доходів і витрат за видами діяльності, що дає змогу охопити всі господарські операції, які здійснює підприємство. Визначено основні завдання організації бухгалтерського обліку витрат, доходів і фінансових результатів, а також об’єкти облікової політики. Описано використання первинних документів для підтвердження здійснення витрат, відображення доходів від реалізації, інших операційних доходів, доходів від участі в капіталі та інших фінансових доходів. Запропоновано модель формування фінансових результатів, організацію аналітичного обліку за рахунками відповідно до кожного виду доходів, витрат і фінансових результатів. The principles of calculation and matching of revenues and expenses. Studies the classification of income and expenses for activities that can cover all business transactions made by the company. Analyzed the content categories of costs, revenues characteristic of all entities regardless of their activity, ownership, size. The results of the critical analysis of the level of compliance methods for determining income and expenses in the accounting systemand their relevance. The main task of accounting of costs, revenues and financial results as well as objects of accounting policies. Shows the use of primary documents for proof of expenses reflection of sales, other operating income, income from investments and other financial income. Reveals the impact of accounting methodology income and expenses for objectivity in determining the financial results of the accounting system. A model of financial results, analytical accounting organization in the context of accounts for each type of revenue expenditure and financial results. Key words: organization of accounting of costs, revenues and financial results, classification activities, classification of costs by activity, by classification of activities, facilities accounting policies for revenue expenditure and financial results, the common objects of accounting policy, the organization of analytical account of revenue expenditure and financial results.
Accounting organization costs, revenues and financial results of the entity
Keywords: організація бухгалтерського обліку витрат; доходів і фінансових результатів; класифікація видів діяльності; класифікація витрат за видами діяльності; класифікація доходів за видами діяльності; об’єкти облікової політики щодо витрат доходів і фінансових результатів; спільні об’єкти облікової політики; організація аналітичного обліку доходів; витрат і фінансових результатів; organization of accounting of costs; revenues and financial results; classification activities; classification of costs by activity; by classification of activities; facilities accounting policies for revenue expenditure and financial results; the common objects of accounting policy; the organization of analytical account of revenue expenditure and financial results